2018
DOI: 10.1016/j.triboint.2018.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis and tribological investigation on TPU and NBR elastomers applied to sealing applications

Abstract: A B S T R A C TThis study investigates the contact temperatures reached due to frictional heating on TPU (Thermoplastic polyurethane) and NBR (Nitrile butadiene rubber) seal surfaces during operation. These elastomers present limited thermal resistance so an excessive temperature rise may affect their tribological performance. Sliding tests of the elastomers against steel cylinders were carried out and the surface temperature evolution was acquired during the tests using a high precision infrared camera. Frict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The TESSA machine has been developed by TEKNIKER to measure the friction, wear, and leakage of the dynamic seals [23][24][25][26][27][28]. It can reach a maximum speed of 6 m/s.…”
Section: The Tessa Machinementioning
confidence: 99%
See 1 more Smart Citation
“…The TESSA machine has been developed by TEKNIKER to measure the friction, wear, and leakage of the dynamic seals [23][24][25][26][27][28]. It can reach a maximum speed of 6 m/s.…”
Section: The Tessa Machinementioning
confidence: 99%
“…The authors also acknowledge the cooperation and/or financing of the industries and research institutions participating in each project. The authors made special mention to those members of the tribology team, that completed their Doctoral Thesis for their contribution to the knowledge generated: Bihotz Pinedo (Tribology of seals 2016) [23][24][25]27], Borja Zabala (high Temperature Tribology (eg. moulds, engines) 2017) [20,22,42,43,46,52], Francesco Pagano, (tribology of ionic liquids and vacuum tribology, 2017) [2-4, 13, 57-65], Beatriz Fernandez-Diaz (tribology of polymers, 2017) [28,34,63], Virginia Saenz de Viteri (biotribology, 2016) [30,31,56,57], Sofia Alves (dental tribology, 2017) [58], Cristina Cerrillo (ecotoxicity of nanoparticles, 2016) [71][72][73][74][75], Ainara López (marine and off shore tribology, 2018) [12][13][14][15][16].…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Pinedo et al. 14 investigated on the influence of frictional heating on the temperature rise and how frictional heating can affect the tribological properties of TPU and NBR elastomers. Recent studies show that upon reduction of reinforcement size to the sub-micron or nano-scale, the wear and friction performance of polymer composites may become significantly better compared to that of micro-particle filled systems.…”
Section: Introductionmentioning
confidence: 99%
“…The friction coefficient, of the 1/3 spherical texture sample with an area density of 38%,was reduced by 64.47% under 0.7 MPa and 250 r/min, and the wear mass was also the lowest. Pinedo et al 13 established the relationship between friction and heat generated during the TPU material friction process. They showed that the friction coefficient and the temperature curve had the same overall tendency, indicating that the surface temperature of the material was related to the friction energy generated.…”
Section: Introductionmentioning
confidence: 99%